Acid-sensing ion channel-1 contributes to axonal degeneration in autoimmune inflammation of the central nervous system. - Friese, M; Craner, M; Etzensperger, R; Vergo, S; Wemmie, J; Welsh, M; Vincent, A; Fugger, L (2007)
Multiple sclerosis is a neuroinflammatory disease associated with axonal degeneration. The neuronally expressed, proton-gated acid-sensing ion channel-1 (ASIC1) is permeable to Na+ and Ca2+, and excessive accumulation of these ions is associated with axonal degeneration. We tested the hypothesis that ASIC1 contributes to axonal degeneration in inflammatory lesions of the central nervous system (CNS). After induction of experimental autoimmune encephalomyelitis (EAE), Asic1-/- mice showed both a markedly reduced clinical deficit and reduced axonal degeneration compared to wild-type mice. Consistently with acidosis-mediated injury, pH measurements in the spinal cord of EAE mice showed tissue acidosis sufficient to open ASIC1. The acidosis-related protective effect of Asic1 disruption was also observed in nerve explants in vitro. Amiloride, a licensed and clinically safe blocker of ASICs, was equally neuroprotective in nerve explants and in EAE. Although ASICs are also expressed by immune cells, this expression is unlikely to explain the neuroprotective effect of Asic1 inactivation, as CNS inflammation was similar in wild-type and Asic1-/- mice. In addition, adoptive transfer of T cells from wild-type mice did not affect the protection mediated by Asic1 disruption. These results suggest that ASIC1 blockers could provide neuroprotection in multiple sclerosis.